2018
DOI: 10.1161/jaha.117.008259
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Mineralocorticoid Receptor Contributes to Epithelial Sodium Channel–Mediated Intestinal Sodium Absorption and Blood Pressure Regulation

Abstract: BackgroundMineralocorticoid receptor (MR) has pathological roles in various cell types, including renal tubule cells, myocytes, and smooth muscle cells; however, the role of MR in intestinal epithelial cells (IECs) has not been sufficiently evaluated. The intestine is the sensing organ of ingested sodium; accordingly, intestinal MR is expected to have essential roles in blood pressure (BP) regulation.Methods and ResultsWe generated IEC‐specific MR knockout (IEC‐MR‐KO) mice. With a standard diet, fecal sodium e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…The MR is activated by the steroid hormone aldosterone, as well as by corticosteroids, when the protecting enzyme 11b-hydroxysteroid dehydrogenase type 2 (HSD2) is not co-expressed. Its main function in the kidneys and colon is to regulate sodium balance and blood pressure [ 1 , 2 , 3 ]. Over the last two decades, several clinical trials have revealed the beneficial effects of MR antagonists (MRAs) in improving the prognosis of cardiovascular disease [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MR is activated by the steroid hormone aldosterone, as well as by corticosteroids, when the protecting enzyme 11b-hydroxysteroid dehydrogenase type 2 (HSD2) is not co-expressed. Its main function in the kidneys and colon is to regulate sodium balance and blood pressure [ 1 , 2 , 3 ]. Over the last two decades, several clinical trials have revealed the beneficial effects of MR antagonists (MRAs) in improving the prognosis of cardiovascular disease [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…NHE3 KO mice are known to have high serum aldosterone (Schultheis, Clarke, Meneton, Miller, et al, 1998). Aldosterone targets the colon through mineralocorticoid receptor (MR) to regulate sodium absorption through NHE3 and ENaC (Nakamura et al, 2018). The NHE3 KO mouse has upregulated expression of the β and γ subunits of ENaC (Schultheis, Clarke, Meneton, Miller, et al, 1998) as do rats with chronic renal failure (Hatch & Freel, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CLDN2, which forms cation-permeable pore, is upregulated by aldosterone mediated through the activation of the mineralocorticoid receptor. The intestinal mineralocorticoid receptor has been recently reported to be involved in the regulation of Na + absorption in the colon using intestinal epithelial cell (IEC)-specific knockout mice [16]. CLDN2 may be involved in the regulation of NaCl absorption by aldosterone.…”
Section: Discussionmentioning
confidence: 99%